2014
DOI: 10.1007/s10067-014-2797-6
|View full text |Cite
|
Sign up to set email alerts
|

Rates of meniscal tearing in patients with chondrocalcinosis

Abstract: Internal derangement of the knee secondary to a meniscal tear has been recently observed in patients with chondrocalcinosis. However, there is no data about the prevalence of meniscal tears associated to chondrocalcinosis. Therefore, the aim of this study was to know the rates of meniscal tear in patients with chondrocalcinosis. The study population was a cohort of 1031 consecutive outpatients who underwent arthroscopy of the knee. Meniscal tear was present in 322 patients and 709 patients had intact meniscus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In a previous study using arthroscopy, the prevalence of meniscal tears in subjects with chondrocalcinosis was comparable to our findings, with complex tears being the most frequent type of tears, followed by horizontal tears [14]. However, subjects were only stratified into subjects with or without chondrocalcinosis for the previous analysis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In a previous study using arthroscopy, the prevalence of meniscal tears in subjects with chondrocalcinosis was comparable to our findings, with complex tears being the most frequent type of tears, followed by horizontal tears [14]. However, subjects were only stratified into subjects with or without chondrocalcinosis for the previous analysis.…”
Section: Discussionsupporting
confidence: 56%
“…Arthroscopically, it has been shown that chondrocalcinosis is associated with meniscal tears [14]. However, MRI is the most accurate and least invasive for diagnosis of cartilage and meniscal damage [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that 86% of patients with CPPD disease displayed calcified mineral deposits in the meniscus and that calcification increased with age [22, 23]. In a previous study conducted in our laboratory, we showed that OA meniscal cells produced more calcium deposits in culture than normal meniscal cells and displayed elevated expression of several genes involved in biomineralization [24].…”
Section: Introductionmentioning
confidence: 92%
“…The absence of crystal shedding in patients with chondrocalcinosis might explained by its deeper location and a firm attachment within the articular cartilage and menisci. [67] On the other hand, synovial membrane is probably an uncommon source for mechanical shedding because crystal deposits in chondrocalcinosis have been identified subsynovially. [7]…”
Section: Discussionmentioning
confidence: 99%